2017
DOI: 10.1111/nep.12809
|View full text |Cite
|
Sign up to set email alerts
|

Severe infections in patients with lupus nephritis treated with immunosuppressants: A retrospective cohort study

Abstract: Serious infections are common among patients with LN and are associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
1
17
3
Order By: Relevance
“…32 It is thus important to minimise occurrence and duration of flares with adequate immunosuppressive therapy, balanced against the risk of immunosuppressant-related complications such as infections. 33 Other studies also identified gender, 13,26,34 proteinuria 13,26,29 and histological class 25 to affect renal progression. Among the eight patients seronegative for both ANA and anti-dsDNA, four had membranous lupus nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 It is thus important to minimise occurrence and duration of flares with adequate immunosuppressive therapy, balanced against the risk of immunosuppressant-related complications such as infections. 33 Other studies also identified gender, 13,26,34 proteinuria 13,26,29 and histological class 25 to affect renal progression. Among the eight patients seronegative for both ANA and anti-dsDNA, four had membranous lupus nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The Ohio SLE study found that renal flare for more than 30% of the follow‐up duration was independently associated with developing new or progressive CKD (odds ratio 20, 95% confidence interval 4.6–91.3) . It is thus important to minimise occurrence and duration of flares with adequate immunosuppressive therapy, balanced against the risk of immunosuppressant‐related complications such as infections …”
Section: Discussionmentioning
confidence: 99%
“…The observed increased risk of infection has been attributed to both SLE itself and the use of immunosuppressant therapies . It has been noted that those with lupus nephritis (LN) may be at higher risk of infection compared to SLE patients without LN . Our prior work has demonstrated that infections were very common and associated with high mortality among adults with SLE enrolled in Medicaid in the US between 2000–2006, and that infection was the second most common cause of death among children with LN‐associated end‐stage renal disease in the US from 1995 to 2006 .…”
Section: Introductionmentioning
confidence: 99%
“…However, intrinsic factors related to the pathophysiology of SLE are implicated in susceptibility to infection in patients with SLE. For example, relapse of lupus nephritis [63] and exacerbation of SLE [64] were demonstrated to be risk factors for infection. Zonana-Nacach et al investigated the risk factors for infection in 200 outpatients with SLE over an average follow-up period of 22 months [65].…”
Section: Risk Factors For Infection In Slementioning
confidence: 99%